Workplace abuse and harassment: the vulnerability of informal and migrant domestic workers in Portugal - Figueiredo, M. C.; Suleman, F.; Botelho, M. C. (Social Policy and Society, 2018)
Policy makers and researchers are alarmed by the pervasive substandard working conditions and mistreatment in domestic work worldwide. Using an original dataset from a sample of domestic workers in Portugal (n=684), our study explores types of abuse and harassment and tries to unveil the potential factors affecting the likelihood of having been a victim. Empirical evidence pointed to three segments of domestic workers: victims of labour abuses related to contract and wages, victims of multiple abuses including mistreatment and also psychological and sexual harassment, and a segment with no occurrence of abuse. Informal workers are more often victims of labour abuses, while migrants, especially Brazilian women, are more likely to report all types of abuse and harassment. On the other hand, carers of the elderly often suffered multiple abuses. The results suggest that despite the prevalence of labour abuses in Portugal, the most severe abuses are uncommon.